Restorative Encounters in Terrorist Victimization in Spain: Theoretical Reflections and Practical Insights from Social Work - Alberto Jose Olalde (Oñati Socio-Legal Series)
After the ceasefire announcement by the terrorist organization ETA in 2011, new horizons and scenarios of peace have opened in the Basque Country, a land that has been badly hurt by violence over several decades.